Biochemical and functional responses stimulated by platelet-activating factor in murine peritoneal macrophages [published erratum appears in J Cell Biol 1988 Sep;107(3):following 1260] (The Rockefeller University Press, 1988)
Platelet-activating factor (PAF) is a potent stimulant of leukocytes, including macrophages. To analyze the mechanisms of its effects upon macrophages, we determined whether macrophages bear specific surface receptors for PAF. By competitive radioactive binding assays, we determined two classes of specific receptors to be present on purified membranes derived from murine peritoneal macrophages (one having a Kd of approximately 1 X 10(-10) M and one a Kd of approximately 2 X 10(-9) M). When the macrophages were incubated with PAF, rapid formation of several inositol phosphates including inositol 1,4,5-trisphosphate and inositol 1,3,4,5-tetrakisphosphate were observed. PAF also elevated intracellular levels of calcium to 290 +/- 27% of basal levels which were 82.7 +/- 12 nM. Increases in calcium were observed first in submembranous areas of the macrophages. PAF also led to increases of 1,2-diacylglycerol of approximately 200 pmol/10(7) cells. A characteristic pattern of enhanced protein phosphorylation, similar to that initiated by both phorbol 12,13-myristate and lipopolysaccharide, was observed and involved enhanced phosphorylation of proteins of 28, 33, 67, and 103 kD. The half-maximal dose of PAF for initiating all the above effects was approximately 5 X 10(-9) M. PAF also initiated significant chemotaxis of the cells; the half-maximal dose for this effect was approximately 1 X 10(-11) M. Taken together, these observations suggest that murine mononuclear phagocytes bear specific membrane receptors for PAF and that addition of PAF leads to generation of break-down products of polyphosphoinositides, subsequent changes in intracellular calcium and protein phosphorylation, and chemotaxis.